5^x+9=134.1^2010
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
e) 96-5(2x-1)=41
5(2x-1)= 96-41
5(2x-1)=55
2x-1=55:5
2x-1=11
2x=11+1
2x=12
x=12:2
x=6
a) Vì \(2010-\left|x-2010\right|=x\)
\(\Rightarrow\left|x-2010\right|=2010-x\)
\(\Rightarrow\left|x-2010\right|=-\left(x-2010\right)\)
\(\Rightarrow x-2010\le0\)
\(\Rightarrow x\le2010\)
Vậy \(x\le2010.\)
b) \(\left|3x-4\right|+\left|3x+5\right|=9\)
\(\Rightarrow\left|4-3x\right| +\left|3x+5\right|=9\)
Nhận thấy \(\left|4-3x\right|\ge4-3x\)
\(\left|3x+5\right|\ge3x +5\)
\(\Rightarrow\left|4-3x\right|+\left|3x+5\right|\ge4-3x+3x+5\)
\(\Rightarrow\left|4-3x\right|+\left|3x+5\right|\ge9\)
Dấu \("="\) xảy ra khi:
\(\left[{}\begin{matrix}4-3x\ge0\\3x+5\ge0\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}3x\le4\\3x\ge-5\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x\le\dfrac{4}{3}\\x\ge\dfrac{-5}{3}\end{matrix}\right.\)
\(\Rightarrow\dfrac{-5}{3}\le x\le\dfrac{4}{3}.\)
Vậy \(\dfrac{-5}{3}\le x\le\dfrac{4}{3}.\)
tính :
a)\(\frac{459}{987}\cdot\left(\frac{1}{4}+\frac{1}{12}-\frac{1}{3}\right)-\frac{2009}{2010}\)
\(=\frac{459}{987}\cdot\left(\frac{3}{12}+\frac{1}{12}-\frac{4}{12}\right)-\frac{2009}{2010}\)
\(=\frac{459}{987}\cdot0-\frac{2009}{2010}\)
\(=\frac{-2009}{2010}\)
b) \(\frac{-9}{7}-\frac{5}{7}\cdot\left[\left(\frac{-2}{3}\right)^2-1\right]\div\frac{-5}{9}\)
\(=\frac{-9}{7}-\frac{5}{7}\cdot\left[\frac{4}{9}-1\right]\div\frac{-5}{9}\)
\(=\frac{-9}{7}-\frac{5}{7}\cdot\frac{-5}{9}\div\frac{-5}{9}\)
\(=\frac{-9}{7}-\frac{5}{7}\)
\(=-2\)
tìm x:
a) \(\left(x-\frac{7}{18}\right)-\frac{15}{27}=\frac{-10}{27}\)
\(\left(x-\frac{7}{18}\right)=\frac{-10}{27}+\frac{15}{27}\)
\(\left(x-\frac{7}{18}\right)=\frac{5}{27}\)
\(x=\frac{5}{27}+\frac{7}{18}\)
\(\Rightarrow x=\frac{31}{54}\)
b) \(\left(3\frac{1}{2}-2x\right)\cdot\frac{11}{3}=7\frac{1}{3}\)
\(\left(\frac{7}{2}-2x\right)\cdot\frac{11}{3}=\frac{22}{3}\)
\(\left(\frac{7}{2}-2x\right)=\frac{22}{3}\div\frac{11}{3}\)
\(\left(\frac{7}{2}-2x\right)=2\)
\(2x=\frac{7}{2}-2\)
\(x=\frac{3}{2}\div2=\frac{3}{4}\)
\(\Rightarrow x=\frac{3}{4}\)
a)(-7 / 5 + 3 / 8 ) : 2009 / 2010 + (-3 / 5+5 / 8) : 2009 / 2010
=[ (-7 / 5 + 3 / 8 ) + (-3 / 5+5 / 8) ] : 2009/2010
=[ -7/5 +3/8 + (-3)/5+5/8 ] : 2009/2010
=[ (-7/5 + (-3)/5) + (3/8 + 5/8) ] :2009/2010
=[-2+1] : 2009/2010
=-1 :2009/2010
=-2009/2010
b)\(\frac{9^8\cdot4^3}{27^4\cdot6^5}=\frac{\left(3^2\right)^8\cdot\left(2^2\right)^3}{\left(3^3\right)^4\cdot\left(2\cdot3\right)^5}=\frac{3^{16}\cdot2^6}{3^{12}\cdot2^5\cdot3^5}=\frac{3^{16}\cdot2^5\cdot2}{3^{16}\cdot3^1\cdot2^5}=\frac{2}{3^1}=\frac{2}{3}\)